Influence of mining-induced ground fissures with different widths on soil anti-scourability in northern Shaanxi coal mining area in the middle reaches of the Yellow River - Shijie SONG; Hao RUAN; Shuangming WANG; Baodeng CHEN; Yuanhong LI; Lu LIU; Jiajie ZHANG (Meitan kexue jishu)
As the most significant and representative form of mining damage in the coal mining area of northern Shaanxi in the middle reaches of the Yellow River, the soil erosion effect caused by mining ground fissures can not be ignored. In order to study the influence of mining-induced ground fissures on the anti-scourability of surrounding soil, the mining-induced ground fissures with widths of 0−10 cm, 10−20 cm and 20−30 cm in the mining-induced ground fissure development area in the north wing of Ningtiaota in northern Shaanxi were selected as the research objects. The surface soil with a horizontal distance of 0−80 cm was collected, and the soil mechanical composition, >0.25 mm water-stable aggregates and organic matter were measured. Five influencing factors of soil anti-scourability and soil anti-scourability coefficient, which are generally concerned by domestic and foreign scholars, reveal the changes of soil physical and chemical properties and anti-scourability coefficient around mining-induced ground fissures. The prediction model of surface soil anti-scour coefficient in the mining ground fissure development area of northern Shaanxi was constructed. The results show that: The sediment loss caused by the erosion of the surface soil around the mining ground fissure will show a three-stage change process of “rapid increase (0−1 min), slow increase (1−3 min) and stable (3−10 min)” with the increase of the erosion time. The sediment loss caused by the erosion mainly comes from within 3 min, and its contribution rate exceeds 90%. Mining-induced ground fissures will have a significant effect on reducing the anti-scourability of the surrounding surface soil, with a maximum decrease of 32.1%, and the greater the width of the mining-induced ground fissures, the closer to the ground fissures, the more obvious the effect. The soil anti-scourability coefficient was significantly negatively correlated with the mass fraction of sand (p<0.01), and was significantly positively correlated with the mass fraction of clay, >0.25 mm water-stable aggregates and organic matter (p<0.01). Among them, the mass fraction of sand, organic matter and >0.25 mm water-stable aggregates can be used as the main controlling factors of soil anti-scourability in the mining ground fissure development area of northern Shaanxi. The prediction model of surface soil anti-scourability coefficient in mining ground fissure development area is constructed by taking the width of mining ground fissure and the horizontal distance from the fissure as variables. It is found that when the horizontal distance exceeds 158 cm, the influence of mining ground fissure on the surrounding surface soil anti-scourability basically disappears, which can be used as the target area for the prevention and control of soil water erosion in the mining ground fissure development area of northern Shaanxi. The research results can provide a scientific basis for the precise prevention and control of soil erosion in the mining area of northern Shaanxi in the middle reaches of the Yellow River.